Fabrication of a 3D combinatorial fibrous-porous scaffold for neural tissue engineering applications - Girão, André F. (2020)
The ability of tissue engineered scaffolds to modulate the response of neural stem cells (e.g. adhesion, proliferation and differentiation) is boosting the unlocking of advanced therapeutic strategies capable of attenuating the effects of traumatic pathologies like spinal cord injury [1]. From the wide range of reported scaffolding concepts, it has been consistently demonstrated that nanofibrous networks and graphene-based porous systems are proficient for guiding neurite outgrowth and inducing specific differentiation patterns, respectively [2].